2018
DOI: 10.1016/j.cbpa.2017.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antioxidants, food deprivation and growth affect differently oxidative status of blood and brain in juvenile European seabass ( Dicentrarchus labrax )

Abstract: Compensatory growth may increase molecular oxidative damage, which may be mitigated through the intake of dietary antioxidants. However, dietary antioxidants may also reduce concentration of antioxidant enzymes, which have a key role in regulating the oxidative status. Here we investigated whether feeding on a diet rich in antioxidants (vitamin E) enables juvenile European seabass (Dicentrarchus labrax) to catch up after a period of food deprivation with negligible effects on the oxidative stress to blood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Yet, as for fast life history in general, there is ongoing debate about the role of oxidative stress in shaping rapid growth and its costs (Christensen et al., 2016; Monaghan & Ozanne, 2018; Smith et al., 2016). While several studies showed compensatory growth to be associated with increased oxidative stress (but see Noguera, Lores, Alonso‐Alvarez, & Velando, 2011), this was mainly based on the levels of antioxidant enzymes (birds: Alonso‐Alvarez, Bertrand, Faivre, & Sorci, 2007; fish: Costantini et al., 2018; damselflies: De Block & Stoks, 2008; ladybirds: Xie et al., 2015; frogs: Burraco, Valdés, & Orizaola, 2020) and very rarely on the direct measurement of oxidative damage (fish: Kim, Noguera, & Velando, 2019; birds: Costantini et al., 2018). Therefore, current evidence is largely inconclusive because levels of antioxidant defence may covary both negatively as positively with oxidative damage (Costantini & Verhulst, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as for fast life history in general, there is ongoing debate about the role of oxidative stress in shaping rapid growth and its costs (Christensen et al., 2016; Monaghan & Ozanne, 2018; Smith et al., 2016). While several studies showed compensatory growth to be associated with increased oxidative stress (but see Noguera, Lores, Alonso‐Alvarez, & Velando, 2011), this was mainly based on the levels of antioxidant enzymes (birds: Alonso‐Alvarez, Bertrand, Faivre, & Sorci, 2007; fish: Costantini et al., 2018; damselflies: De Block & Stoks, 2008; ladybirds: Xie et al., 2015; frogs: Burraco, Valdés, & Orizaola, 2020) and very rarely on the direct measurement of oxidative damage (fish: Kim, Noguera, & Velando, 2019; birds: Costantini et al., 2018). Therefore, current evidence is largely inconclusive because levels of antioxidant defence may covary both negatively as positively with oxidative damage (Costantini & Verhulst, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, dietary antioxidants might impact the host's capacity to cope with an infectious disease because antioxidants reduce immunopathology associated with the immune/inflammatory response (Dhinaut, Balourdet, Teixeira, Chogne, & Moret, ); they occur in limited supply for free‐ranging animals, potentially constraining their capacity to cope with oxidative stress (Catoni et al, ; Costantini, Angeletti, et al, ) and may limit steroid synthesis (Ozdemir, Ozudogru, Imik, Can, & Sunar, ). Accordingly, antioxidants can inhibit the replication of several viruses (i.e., feline immunodeficiency virus Mortola et al, ; influenza virus Han et al, ; duck enteritis virus Xu et al, ; herpes simplex virus Civitelli et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative damage, however, remained unchanged across sites possibly because chipmunks allocated resources to other traits of functions instead of minimizing oxidative damage, as observed in other studies. For instance, supplementation studies showed that extra resources available for juveniles were used to maximise growth rates, sometimes at the cost of oxidative status regulation (Costantini et al, 2018; Giordano, Costantini & Tschirren, 2015; Hall et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative status regulation can fluctuate according to external factors such as food availability. Increased food availability has been shown to increase antioxidant capacity and/or decrease oxidative damage (Costantini et al, 2018; Costantini et al, 2009; Fletcher et al, 2013; Van de Crommenacker et al., 2011). This could be due to an increase in exogenous antioxidant intake, an increase in endogenous antioxidant synthesis or lower foraging efforts (Beaulieu & Schaefer, 2013; Catoni, Peters & Schaefer, 2008; Lee et al, 2013; Li et al, 2014; Smith, Nager & Costantini, 2016; Van de Crommenacker et al., 2011).…”
Section: Introductionmentioning
confidence: 99%